Peabody Developmental Motor Scales - Second Edition (PDMS-2): Reliability, content and construct validity evidence for Brazilian children. (April 2021) - Zanella, Larissa Wagner; Valentini, Nadia Cristina; Copetti, Fernando; Nobre, Glauber Carvalho
Highlights: Validity evidence of Peabody Developmental Motor Scales-Second Edition (PDMS-2) for Brazilian large sample of children. The PDMS-2 administered to the Brazilian population has psychometric characteristics equivalent to the original version. Motor development can be monitored and evaluated, by teachers and health professionals, safely through the PDMS-2. Abstract: Background: The Peabody Developmental Motor Scales - Second Edition (PDMS-2) has been used by health and educational professionals to assess the gross and fine motor skills of children with typical development, motor and/or cognitive delays, and disabilities. Aim: Investigate the validity and reliability of PDMS-2 for use in Brazil. Methods: For content validity, 13 professionals participated in the study. For construct validity, a sample of 637 children from birth until 71 months (0–23 months: n = 399; 24–71 months: n = 238) was assessed with the PDMS-2. Results: The PDMS-2 administered to the Brazilian population has psychometric characteristics equivalent to the original version. Conclusion: PDMS-2 is a valid and reliable tool for evaluating Brazilian children's motor development and providing appropriate support for clinical and educational intervention plans and follow-ups.